Program penyusunan standar operasional prosedur bumdes untuk peningkatan kualitas pelayanan pada Desa Koto Sentajo, Kabupaten Kuantan Singingi - Annisa Mardatillah; Rosmayani Rosmayani (PELANTAR PRESS, 2021)
The existence of BUMDes BUMDes as a successful social institution is expected to contribute to the provision of all social service efforts to the community. In addition, as a commercial institution, BUMDes aims to provide benefits from every commercial business carried out that contributes to each of its business activities and favors the interests of the community. Achieving success, the professional implementation and management of BUMDes need to be carried out with a good, transparent, and sustainable level of accountability as a serious effort to make BUMDes run independently, effectively, and efficiently. In order to achieve this, it is, of course, essential for BUMDes to prepare Standard Operating Procedures (SOPs) that suit the needs of each business unit effectively and efficiently. The problem of limited knowledge and skills of Community Service (PKM) partners related to preparing effective and efficient SOPs is overcome through this PKM activity. This community service activity with PKM BUMDes Sumber Berkah partners is carried out with counseling methods and basic training to recognize the steps for preparing BUMDes SOPs following SOP principles to improve the quality of BUMDes services. The achievement of the target of this PKM activity is an increase in the knowledge and skills of partners in formulating SOPs effectively and efficiently.